Analyze the factors that affect the learning of first year physics students - LATHSAATH, Boupheng; VANHMIXAY, Khamsing; SAYCOCIE, Pasaykhone; SAYASONE, Phouratsamay; PHETSOMPHOU, Phonesin (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this scientific research entitled "Analysis of Factors Affecting Students 'Learning" was to analyze the factors that affect students' learning outcomes in the Department of Physics, first year 2015-16. The researchers identified three target groups: The first group consisted of 32 first-year physics students who were the first generation students of the Department of Physics, Faculty of Natural Sciences, Savannakhet University. Using questionnaires with questionnaire scoring the second group is the 13 classroom teachers who teach regularly in the school year (internal and guest teachers). And the third group is the parents or guardians of 32 families of students but actually answered only 15 questionnaires. Identify 3 main factors: the internal condition of the student (the basic factor of the student); Family (parental background) and student centered learning environment. Use the tools with the three groups of questionnaires and then analyze the descriptive statistics, such as Mean; Standard conversion fee (Std) and CV fee (CV). For reference statistics use Microsoft Excel or SPSS To fine Multiple-R and p-value <0.05. The results of the analysis of the results of the students who were ranked from the largest value to the smallest value of all four factors found that: The best factor is the warmth and encouragement of parents is average Subsequent support factors were average Next, family factors were averaged The weakest factor is the factor in the condition of natural science teachers in the average graduate school.